Integrasi Teknologi Interaktif dalam Perancangan Sistem Pembelajaran Digital Berbasis Web - Prizca Asty Andreana; Devi Putri Febriyanti; Anggi Novellia Zulva; Edy Susena (Jurnal Kendali Teknik dan Sains, 2025)
This research iss motivated by the problem of the lack of digital learning facilities that can be flexibly accessed by students and theachers at SMP Djama'atul Ichwan Surakarta, so that interaction in the theaching and learning proces is limited. The theories applied in this study include the concept of E-Learning as a distance learning method rooted in information technology, web-based system development, and an interactive technology integration approach to increase effectiveness and engagement in learning. The method used is the Waterfall model system development life cycle (SDLC), which includes the stages of needs analysis, system design, implementation with PHP and MySQL using the CodeIgniter framework, and function testing. The research findings show that the designed web-based E-Learning system successfully provides features for managing student and teacher data, distributing teaching materials, scheduling lessons, giving assignments, and interaction through discussion forums. This system is considered capable of supporting a more organized and interactive online education process.The implementation of this systemis expected to a long-term solution to overcome the limitations of traditional learning methods and become a foundation for the development of digital learning platforms in the futur.